2020
DOI: 10.1016/j.jns.2019.116510
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical associations of disproportionately enlarged subarachnoid space hydrocephalus (DESH), an imaging feature of idiopathic normal pressure hydrocephalus in community and memory clinic based Singaporean cohorts

Abstract: Introduction: Disproportionately Enlarged Subarachnoid space Hydrocephalus (DESH) is considered as an important imaging feature of idiopathic normal pressure hydrocephalus (iNPH). Method: Subjects aged 60 and over in a memory clinic and a community-based cohort were assessed for the presence of ventriculomegaly, Sylvian dilatation, and high convexity tightness by neuroimaging, and a clinical triad of iNPH symptoms, i.e. cognitive, gait and urinary symptoms. Results: In the memory clinic-based study (548 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
10
2
Order By: Relevance
“…Although CSF dynamics disorders have been under-appreciated in clinical and research setting, awareness is beginning to grow. Recent studies have shown the prevalence of DESH imaging features to be approximately 1–7% in community-based populations ( Akiba et al, 2020 ; Graff-Radford et al, 2019 , ; Hiraoka et al, 2008 ; Jaraj et al, 2014 ). Although less common than Alzheimer’s disease or cerebrovascular disease, CSF dynamics disorders warrants consideration in evaluation of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CSF dynamics disorders have been under-appreciated in clinical and research setting, awareness is beginning to grow. Recent studies have shown the prevalence of DESH imaging features to be approximately 1–7% in community-based populations ( Akiba et al, 2020 ; Graff-Radford et al, 2019 , ; Hiraoka et al, 2008 ; Jaraj et al, 2014 ). Although less common than Alzheimer’s disease or cerebrovascular disease, CSF dynamics disorders warrants consideration in evaluation of cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…DESH has been found to predict clinical improvement in NPH symptomatology following CSF shunting ( Hashimoto et al, 2010 ; Narita et al, 2016 ). DESH has since been more widely recognized in the community and has been found to be associated with worse cognition ( Akiba et al, 2020 ; Graff-Radford et al, 2019 ; Hiraoka et al, 2008 ). Although few studies have shown the presence of DESH imaging features in community or non-NPH study populations, the clinical significance of DESH with regard to cognitive decline outside of NPH is not yet well defined.…”
Section: Introductionmentioning
confidence: 99%
“…After the introduction of guidelines, only the patients who fulfilled the radiological diagnostic criteria have been selected for shunt surgery. [ 7 8 13 27 28 29 30 31 32 ] It has been difficult to verify the validity of EI >0.3 as the radiological diagnostic criteria for iNPH. Naruse and Matsuoka reported the symptoms of all the 14 patients improved remarkably by shunt despite EI ≤0.3.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have now investigated the presence of DESH in the wider population, where it is found in 1–7% and associated with poorer cognition ( 49 52 ). A study examining over a thousand participants with either no or only mild cognitive impairment found that DESH was a predictor of progressive cognitive decline independent of established features including age, cortical thickness, or APOE status ( 48 ).…”
Section: Imagingmentioning
confidence: 99%